Korosi Alumunim dalam larutan asam sitrat - Andreas Yoppy Aprianto Prasetya; Isdiriayani Nurdin (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2012)
The corrosion of Allumunium in citric acid sollutionCitric acid is a carboxylic acid that is widely used as an additive in the beverage industry. Aluminum cans are often used as a beverage packaging due to its lightweight, space efficient, and low production costs. Contact between citric acid and the aluminum cans may cause corrosion reactions that lead contamination of beverages by corrosion products. This study aims to test the aluminum resistance against citric acid at the concentration of 1, 2, and 4 %-wt, and temperature of 40 °C, 50 °C, and 60 °C. The specimen used is a 1 cm2 aluminum plate with a purity of 99.07%. The experiment consists of aluminum corrosion rate measurements using the Tafel method and aluminum corrosion mechanism prediction using cyclic-voltammetry method. The research results show that aluminum is corroded into Al3+ by citric acid solution in a one-stage reaction with activation energy of 65.01 kJ/mol. The corrosion products are not stable, it forms amorphous aluminum salts. The aluminum corrosion rate increases with rising citric acid concentration and temperature that can be classified in